Differences in HBV Replication, APOBEC3 Family Expression, and Inflammatory Cytokine Levels Between Wild-Type HBV and Pre-core (G1896A) or Basal Core Promoter (A1762T/G1764A) Mutants - Lau, Keith C. K.; Joshi, Shivali S.; Mahoney, Douglas J.; Mason, Andrew L.; van Marle, Guido; Osiowy, Carla; Coffin, Carla S. (Frontiers in Microbiology, 2020)
Background: Chronic hepatitis B virus (HBV) infection is the leading cause of hepatocellular carcinoma (HCC) world-wide. HBV variants, particularly the G1896A pre-core (PC) and A1762T/G1764A basal core promoter (BCP) mutations, are established risk factors for cirrhosis and HCC, but the molecular biological basis is unclear. We hypothesized that these variants result in differential HBV replication, APOBEC3 family expression, and cytokine/chemokine expression. Methods: HepG2 cells were transfected with monomeric full-length containing wild-type, PC, or BCP HBV. Cells and supernatant were collected to analyze viral infection markers (i.e., HBsAg, HBeAg, HBV DNA, and RNA). Cellular APOBEC3 expression and activity was assessed by quantitative real-time (qRT)-PCR, immunoblot, differential DNA denaturation PCR, and sequencing. Cytokine/chemokines in the supernatant and in serum from 11 CHB carriers (4 non-cirrhotic; 7 cirrhotic and/or HCC) with predominantly wild-type, PC, or BCP variants were evaluated by Luminex. Results: HBeAg expression was reduced in PC and BCP variants, and higher supernatant HBV DNA and HBV RNA levels were found with A1762T/G1764A vs. G1896A mutant (p<0.05). Increased APOBEC3G protein levels in wild-type vs. mutant was not associated with HBV covalently closed circular DNA G-to-A hypermutations. Differences in cytokine/chemokine expression in culture supernatants, especially IL-13 were observed amongst the variants analyze. Noticeable increases of numerous cytokines/chemokines, including IL-4 and IL-8, were observed in ex vivo serum collected from CHB carriers with PC mutant. Conclusion: HBV sequence variation leads to differences in HBV protein production (HBeAg) and viral replication in addition to altered host innate antiviral restriction factor (APOBEC3) and cytokine/chemokine expression.